Cost-effectiveness of preventive treatment regimens for latent tuberculosis infection among key community-level populations - Jiang, Hualin; Li, Rui; Zhang, Tianhua; Wang, Qinghu; Liu, Haini; Hua, Zhongqiu; Zhang, Shaoru; Zheng, Xiao; Zhuang, Guihua; Shen, Mingwang (BMC medicine, 2025)
Background: Expanding tuberculosis preventive treatment (TPT) for high-risk populations with latent tuberculosis infection (LTBI) is a key component of the End TB Strategy. However, the high-risk population size is small, which may have limited impact on reducing TB incidence. We aimed to evaluate the health impact and cost-effectiveness of expanding TPT to key community-level population. Methods: We developed a dynamic transmission model incorporating the effect of TPT and seasonal variations in TB incidence. The model was calibrated by monthly pulmonary tuberculosis (PTB) case data during 2011–2018 from Shaanxi province, China, and validated by data in 2019. We first assessed the TB epidemic trend for seven expanding TPT strategies and sought the optimal TPT strategy that can reach the target of the End TB Strategy by 2035. Then, we calculated the incremental cost-effectiveness ratios (ICER) of this optimal TPT strategy with five TPT regimens (isoniazid monotherapy with two different durations, rifampin monotherapy, and combinations of isoniazid with rifampin or rifapentine) over 2025–2050, compared with no TPT, from a health system perspective. A willingness-to-pay threshold of US $ 36,378 (three times the per-capita gross domestic product of Shaanxi province in 2023) was used. Results: The optimal TPT strategy is implementing TPT for all WHO-recommended populations and individuals with LTBI aged ≥ 50 at the community level (starting in 2025 with full coverage within 1 year), which could reduce the PTB incidence rate to 1.83/100,000 by 2035, meeting the WHO target of a 90% reduction (5.64/100,000) compared with 2015. This strategy with five TPT regimens was all cost-effective compared with no TPT, with ICER ranging from US $154 (3 months of daily rifampicin plus isoniazid, 3HR) to US $ 910 (9 months of daily isoniazid monotherapy, 9H) per quality-adjusted life-year (QALY) gained. Conclusions: Rapid TPT implementation for all WHO-recommended populations and individuals with LTBI aged ≥ 50 at the community level is critical to achieving TB elimination by 2035. The 3HR regimen, widely performed in clinical practice in China, offers the greatest cost-effectiveness, which provides health economic evidence to expand this regimen further.
Veröffentlicht: 29. Oktober 2025
Gesehen am 05.12.2025